Improving the Quality of Catimor Coffee: Design and Validation of a Dedicated Fermentation Machine - Adauto Sanchez, Cristhian Carlos (2024)
Abstract—This study focused on the development of a coffee fermenting machine designed to enhance the organoleptic characteristics of the Catimor variety in the province of Chanchamayo, with the aim of increasing the value of Peruvian coffee in the international market. The implementation of this machine not only benefits local coffee farmers by improving their income, but also contributes to the consolidation of Peruvian coffee as one of the best in the world. The methodology adopted for the design process follows the guidelines of the German VDI 2221 standard, which allowed for an effective understanding of the steps required to complete the proposed design. Furthermore, the designed machine manages to reduce the fermentation time from approximately 24 to 12 hours, while improving the sensory properties of the coffee when tasted. The design approach was based on a thorough analysis of the needs of coffee farmers in Chanchamayo. This innovative project in fermentation technique was based on mimicking the fermentation process of the coati's digestive system, which allowed the addition of fruity aromas to the coffee beans. In the validation test, an increase of 5.25 points in organoleptic characteristics was achieved, thus meeting the objectives set. This progress will benefit the coffee-growing community of Chanchamayo by improving the yield in the cup, which in turn will increase the price of the product on the market.